2012
DOI: 10.1007/s11999-012-2296-5
|View full text |Cite
|
Sign up to set email alerts
|

Neer Modification of Open Bankart Procedure: What are the Rates of Recurrent Instability, Functional Outcome, and Arthritis?

Abstract: Background Neer modified the Bankart procedure by combining a superoinferior capsular shift with the labral reattachment. The theoretical advantages of the modification were that such a procedure would restore the patient's anatomy and also treat the repeated capsular stretching encountered in anteroinferior instability without limiting external rotation and, thereby reducing the risk of arthritis. Questions/purposes We therefore determined: (1) the rate of recurrent instability after this modification, (2) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…The current study has shown that the glenoid labrum has a rich blood supply, which supports the excellent outcomes of glenoid labrum healing and joint re-instability observed, regardless of the types of the glenoid labrum lesions or their management. [33][34][35][36][37]10 It is suggested that the blood supply to the glenoid labrum is thus sufficient to enable its reattachment. On the other hand, it could be questioned how and why incomplete or non-healing of labrum injuries occurs, leading to recurrent shoulder instability and poor blood supply to the glenoid labrum, such as in diabetic patients, which could impair healing of the glenoid labrum.…”
Section: Discussionmentioning
confidence: 99%
“…The current study has shown that the glenoid labrum has a rich blood supply, which supports the excellent outcomes of glenoid labrum healing and joint re-instability observed, regardless of the types of the glenoid labrum lesions or their management. [33][34][35][36][37]10 It is suggested that the blood supply to the glenoid labrum is thus sufficient to enable its reattachment. On the other hand, it could be questioned how and why incomplete or non-healing of labrum injuries occurs, leading to recurrent shoulder instability and poor blood supply to the glenoid labrum, such as in diabetic patients, which could impair healing of the glenoid labrum.…”
Section: Discussionmentioning
confidence: 99%
“…This reconstruction is a modification of the Putti-Platt, Bankart, and Neer capsular shift procedures. 1,9 One drawback of any capsular shift is the loss of ROM, particularly external rotation. 20 The mean loss of external rotation has been reported to be 13.8º (range, 0º-24º) 8 and 7º, 9 whereas in our patients, no significant loss of ROM was detected after 13 years.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomic reconstruction of the subscapularis tendon, as with the Neer and Rockwood techniques, is more favourable for ROM recovery than techniques that rely on mediolateral soft tissue tightening (Putti-Platt) or subscapularis retensioning (Magnuson-Stack). 1,3 The rate of recurrent dislocation has been reported to be 0% to 57%. Predictors for recurrence include voluntary instability, previous surgical procedures, age at the time of surgery, the presence of labral tears and bone lesions (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations